2008
DOI: 10.1097/cji.0b013e3181833818
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Dendritic Cell Vaccination of Patients With Metastatic Renal Cell Carcinoma

Abstract: Therapeutic dendritic cell (DC) vaccination against cancer is a strategy aimed at activating the immune system to recognize and destroy tumor cells. In this nonrandomized phase 1/2 trial, we investigated the safety, feasibility, induction of T-cell response, and clinical response after treatment with a DC-based vaccine in patients with metastatic renal cell carcinoma. Twenty-seven patients with progressive cytokine-refractory metastatic renal cell carcinoma were vaccinated with DCs loaded with either a cocktai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 43 publications
4
55
0
8
Order By: Relevance
“…This study showed positive immune responses in 10 of 14 patients, along with anecdotal clinical responses [67]. DC loaded with both survivin and telomerase peptides have been tested in renal carcinoma where 13 of 27 patients experienced disease stabilization for 8 weeks along with 1 patient who had stable disease for 6 months [68,69]. In another study, DC pulsed with survivin and MAGE3 mRNA produced vaccinespecific CD3+ T cell production in multiple myeloma patients [70].…”
Section: Survivin Vaccines In Clinical Studiesmentioning
confidence: 72%
“…This study showed positive immune responses in 10 of 14 patients, along with anecdotal clinical responses [67]. DC loaded with both survivin and telomerase peptides have been tested in renal carcinoma where 13 of 27 patients experienced disease stabilization for 8 weeks along with 1 patient who had stable disease for 6 months [68,69]. In another study, DC pulsed with survivin and MAGE3 mRNA produced vaccinespecific CD3+ T cell production in multiple myeloma patients [70].…”
Section: Survivin Vaccines In Clinical Studiesmentioning
confidence: 72%
“…Berntsen and coworkers reported serum YKL-40 to associate with poor prognosis in patients with metastatic RCC treated with experimental dendritic cell vaccination therapy; YKL-40 levels increased significantly within the first four weeks of the treatment, with higher increase being in patients with progressive disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck [18,22,62] Lung cancer (small cell carcinoma) Lung [133,134] Breast cancer Breast Colorectal cancer Colon [20,132] Kidney tumor Kidney [132,142,143] Hepatocellular carcinoma Liver [21,66] Ovarian tumor, endometrial cancer Ovary [55][56][57][58][59][60][61]133,138,139] Primary prostate cancer Prostate [23,63,144] Metastatic prostate cancer Papilloma thyroid carcinoma, thyroid tumor Thyroid [136,145] Extracellular myxoidchondrosarcoma Bone [146] Multiple myeloma Bone marrow [147,148] Hodgkin's lymphoma Lymph node [65] Malignant melanoma Melanocyte [18,64] Myxoid liposarcoma Fat cells [146] 5252 ISSN 1007-9327 CN 14-1219/R World J Gastroenterol November 14, 2009 Volume 15 Number 42…”
Section: Glioma Oligodendroglioma Glioblastomamentioning
confidence: 99%